Digital transformation in logistics: A case study of The Lorry - Awee, Azeyan; Adrus, Norharyani; Lai Ka Fei; Maznorbalia, Anisa Safiah; Awalluddin, Muhammad Aiman; Ab. Wahab, Nur Yuhainis (Journal of Islamic, Social, Economics and Development, 2025)
This case study examines TheLorry, a digital logistics platform founded in 2014 by Nadhir Ashafiq Zainal Abidin and Goh Chee Hau, which has transformed the lorry rental industry with its innovative digital platform. TheLorry, which serves Malaysia's competitive logistics business, uses technology to improve processes, increase transparency, and maximize efficiency. The platform provides customers with on-demand access to verified lorry, truck, and van owners, allowing them to schedule transportation services online while increasing service providers' exposure and employment chances. Strategic collaboration, continuous innovation, and a customer-centric attitude are critical to its success. TheLorry uses AI, IoT, and cloud-based platforms to customize services and develop trust. To attract and keep customers, it utilizes a dynamic pricing strategy as well as digital marketing methods. Despite competition from big companies and operational concerns, TheLorry is expanding geographically and experimenting with new technologies and partnerships. The company's efforts to increase service quality and operational efficiency have established it as a prominent participant in the Southeast Asian logistics sector, with plans for future expansion and technology integration. This study provides insights into TheLorry’s practices, success factors, and challenges, offering valuable lessons for digital entrepreneurship in the logistics industry